Vertical Cylinder Density and Toppling Effects on Dune Erosion and Overwash - Ayat, Berna; Kobayashi, Nobuhisa (ASCE-AMER SOC CIVIL ENGINEERS, 2015)
Interactions among waves, sand dunes, and vertical cylinders are investigated in a laboratory experiment. A cross-shore numerical model is expanded to include the drag force acting on cylinders. The hydrodynamic variables modified by the cylinders are used to predict bed load and suspended sand transport rates. The expanded model is compared with five previous tests. The drag coefficient is calibrated to obtain similar agreement for the dunes with and without the cylinders. Four tests were conducted to examine the placement density and toppling of the cylinders. The effectiveness of the cylinders in reducing dune erosion and overwash decreased significantly with the density decrease and cylinder toppling. The reduced effectiveness is reproduced by the expanded model with the calibrated drag coefficient. However, a simple toppling criterion needs to be adjusted for each test for the reproduction of the observed landward progression of cylinder toppling during the dune profile evolution. Field data will be required to improve the model for real woody plants. (C) 2014 American Society of Civil Engineers.
Keywords: Cylinder; Drag force; Dune; Erosion; Sediment transport; Wave overtopping; Engineering; Water Resources